«Կտակ չարչարանաց»-ի կամ Ավագ ուրբաթի քարոզի՝ Սիմեոն Ա. Երևանցի կաթողիկոսի խմբագրությունը - Հարությունյան, Գառնիկ Ա. (Մատենադարան)
One of the remarkable works belonging the genre “Testament of the Passion [of Christ]” or the sermons of Good Friday belongs to the Catholicos of All Armenians Simeon I Erewants‘i (1710–1763–1780), a famous theologian and clergyman of the Armenian Church of the 18th century. It has reached us in his unpublished Book of Sermons. This book and generally the sermons of Simeon I Erewants‘i are extant in many copies. For example, Matenadaran houses around ninety manuscripts containing his sermons entirely or partially. Also, it is important to mention his autograph, M 2212, which contains his Works. In this article, it is demonstrated that no other original manuscripts are known at the moment, as was considered before. The dates in the autograph of Simeon Erewants‘i (then vardapet, i.e. archimandrite, later bishop) show that the book was written gradually, in Ējmiatsin and Constantinople. While being the legate of the Catholicosate of Ējmiatsin in Constantinople, Simeon Erewants‘i, simultaneously with his ecclesiastical-political and social activities, had opportunities to preach in various eparchies and among the Armenians of Constantinople. Being acquainted with the Armenian Patriarch of Constantinople of that time Hakob Nalyan (1706–1764), Simeon probably knew his version of the “Testament.” One can suppose the same regarding the other recensions (published or unpublished), especially the ones that were written before the 1750s in Constantinople. The sermon of our interest (the 52nd one) has the main characteristics of the genre of “Testaments”, which was already formed by the time it was edited by Simeon Erewants‘i. Such features are the same plot, mixed verse and prose, as well as unofficial style and vocabulary close to oral speech. At the same time, like any other recension of the genre, this one too has differences from the others. We have tried to summarize and present the main characteristics of the “simeonic” recension of the genre of “Testaments.” The manuscripts, structure, plot and linguistic features are discussed in the article. At the same time, we’ve drawn parallels with other versions: by Patriarch Hakob Nalyan (or attributed to him), deacon Stepʻanos Tpʻghisets‘i (Tʻiflizetsʻi), the one included in the Book of Sermons by Grigor Tatʻewats‘i (1346–1409), and the other version preserved in the Lectionary (Chashots‘) of the Armenian Church. The study of each next recension can be compared with the discovery of a tessera in a mosaic, which lets us enrich our knowledge of the religious and theological thought of the given period. Один из примечательных вариантов “Завещания страстей [Христовых]...” или проповедей Страстной пятницы принадлежит перу Католикоса Всех армян Симеона I Ереванци (1710-1763-1780), выдающегося богослова и клирика Армянской церкви XVIII века. Это сочинение дошло до нас в неопубликованном Сборнике проповедей автора. Упомянутый Сборник проповедей и в целом проповеди Симеона Ереванци сохранились во многих списках. Например, только в Матенадаране около девяноста рукописей содержат его проповеди целиком или частично. Среди них имеется единственный известный сегодня автограф – рукопись Матенадарана № 2212, содержащая “Сочинения” автора. Даты, упомянутые в автографе Сборника проповедей Симеона Ереванци (тогда “вардапета”, то есть архимандрита, позже епископа) показывают, что сборник писался постепенно, в Эчмиадзине и Константинополе. В качестве легата Эчмиадзинского Католикосата в Константинополе, Симеон Ереванци, параллельно с церковно-политической и общественной деятельностью, имел возможность проповедовать в разных епархиях и для константинопольских армян. Естественно предположить, что Симеон, знакомый с тогдашним Армянским Патриархом Константинополя, Акобом Наляном (1706-1764), знал о существовании его версии “Завещания” и о других (как рукописных, так и опубликованных) редакциях, особенно возникших до 1750-ых годов в Константинополе. Интересующая нас проповедь (52-ая в Сборнике проповедей) имеет основные особенности жанра “Завещаний”, который был уже сформирован в момент создания редакции Симеона Ереванци. Такими характерными чертами являются одинаковый сюжет, смешанная прозаично-стиховая структура, неофициальный стиль и лексика, приближенная к разговорной речи. В то же время, как и любой образец данного жанра, этот тоже имеет свои особенности. В статье сделана попытка представить основные особенности “симеоновой” редакции “Завещания”: рукописи, структуру сочинения, его сюжет, лингвистические особенности. Эта редакция сопоставлена с другими вариантами «Завещания»: с тем, что принадежит перу или приписывается Патриарху Акобу Наляну; с вариантом дьякона Степаноса Тпхисеци (Тифлисеци); с образцами, сохраненными в Сборнике проповедей Григора Татеваци (1346-1409) и в Лекционарии Армянской церкви (Чашоц). Исследование каждого следующего варианта “Завещания страстей...” можно сравнить с раскрытием новой тессеры в мозаике, которая обогощяет наши знания о религиозной и богословской мысли данной эпохи.
Keywords: Բանասիրություն